2001
DOI: 10.1136/adc.85.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of breathing and associated central autonomic dysfunction in the Rett disorder

Abstract: (Arch Dis Child 2001;85:29-37)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
227
0
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(249 citation statements)
references
References 27 publications
11
227
0
11
Order By: Relevance
“…Several reasons could explain the lack of clinically significant effects of DMI on breathing patterns in RTT girls. First, as described by several authors, breathing dysfunction in RTT is very complex and highly variable 5, 6, 7, 8, 22. We monitored the breathing disorders in awake patients at each visit and found similar results on AHI to those reported in two patients with atypical Rett 23.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Several reasons could explain the lack of clinically significant effects of DMI on breathing patterns in RTT girls. First, as described by several authors, breathing dysfunction in RTT is very complex and highly variable 5, 6, 7, 8, 22. We monitored the breathing disorders in awake patients at each visit and found similar results on AHI to those reported in two patients with atypical Rett 23.…”
Section: Discussionsupporting
confidence: 57%
“…Among the symptoms of RTT, breathing dysrhythmia may represent a life‐threatening event 3. Breathing disorders are present in 65 to 93% of the patients and characterized by hyperventilation, hypoventilation, breath holds and apneic events 4, 5, 6, 7, 8. Studies in validated mouse models of RTT have shown that Mecp2 null male and heterozygous female mice exhibited breathing disturbances with different level of severity 9, 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by normal early development followed by regression, leading to loss of spoken language and/or purposeful hand use, gait abnormalities, and development of stereotypic hand movements. Other common features include growth retardation, seizures, breathing abnormalities, vasomotor disturbances, and abnormal behavior 1, 2, 3, 5, 6, 7, 8. The current standard of care is symptomatic management, with no available treatments aimed at ameliorating the cardinal symptoms of the disorder 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evidence indicates that RTT patients suffer from reduced cardiac vagal tone that can cause life threatening cardiac arrhythmias (34). To examine heart rate abnormalities in MeCP2 -/y mice and the effect of (1-3)IGF-1 treatment, we monitored real time cardiac pulse rate in nonanesthetized wild-type and MeCP2 -/y animals treated with vehicle or (1-3)IGF-1 (Fig.…”
mentioning
confidence: 99%